Efforts by the Patrol Unit of the Samapta Division of Jepara Police to Prevent Motor Vehicle Theft Crimes in Jepara Regency. - Muhammad Abel Putra Mirzan (Akademi Kepolisian Republik Indonesia, 2023)
The author raises the final task with the problem